Artificial Intelligence and Its Impact on Copyright: A Legal Perspective - Furfaro, Ricardo Daniel (European Scientific Journal, ESJ, 2025)
The aim of this research paper is to provide an overview of the current impact of Artificial Intelligence (AI) on copyright, focusing exclusively on AI-generated works that may be eligible for copyright protection. A central dilemma arises concerning the certainty of copyright-specifically, who owns the copyright in works produced through the use of AI systems. Copyright is a legal concept describing the rights granted to creators of literary and artistic works, including reproduction, copying, performance, and public display. The growing role of technology in creative processes has significantly expanded and, in some instances, replaced aspects of human involvement. New creative works generated through software programs built on algorithms and databases can no longer be easily distinguished from those produced by human creators. This situation has created substantial uncertainty in both business and legal spheres. The scope of this article includes (a) an analysis of how key international legal systems address AI-generated creations and their implications for copyright; (b) the identification of possible solutions that governments may adopt to promote legislative uniformity; and (c) an evaluation of how such uniformity could strengthen legal certainty and support ethics and the public interest. This study follows an explorative, descriptive, qualitative methodology to examine how different countries have approached AI-related legislation, including regulations and enacted laws. The research emphasizes the principles of legal certainty, ethics, and the protection of the public interest. Findings indicate that countries across different regions are at varying stages in their approach to AI. In the United States, AI-generated works created without human input are not copyrightable. In contrast, Chinese courts have ruled that human intellectual involvement coupled with originality may justify copyright protection for AI-generated works. The United Kingdom (UK) has adopted a more flexible approach, granting copyright to the individual who makes the necessary arrangements for the creation of a work. Overall, North American and European countries have taken the lead. There is a pronounced focus on ethics and the protection of public interest, as reflected in the Global State of Responsible AI Report (2024).